Global Trends and Hotspots in Trigeminal Neuralgia Research From 2001 to 2021: A Bibliometric Analysis - Zhu, Ganggui; Fu, Zaixiang; Su, Sheng; Tang, Yajuan; Liu, Fuyi; Yu, Wenhua (Frontiers in Neurology, 2022)
Background:In recent years, there has been an increasing number of studies on trigeminal neuralgia(TN). However, there is a lack of scientific and comprehensive research on the current status and trends in the field of TN research. The purpose of this study is to summarize and visualize the development, research hotspots and future trends in TN based on a bibliometric approach. Methods:Studies on TN published from 2001-2021 were obtained from the Web of Science Core Collection (WoSCC). Bibliometrix, Citespace and VOSviewer tools were used for bibliometric analysis and visualization. Results:In total, 4112 documents were searched. The number of research articles on the field is generally on an upward trend, with the fastest growth in the number of articles from 2017 to 2020. Shanghai Jiao Tong University, Pittsburgh University and Mayo Clinic are the three institutions with the most publications. Shiting Li and Zakrzewska JM are the most prolific author and top co-cited author respectively.The Journal of Neurosurgery is the most influential journal. Top 5 keywords in that time frame are TN, microvascular decompression, facial pain, stereotactic radiosurgery and neuropathic pain. Conclusion:This is the first comprehensive scientific bibliometric analysis of the global research field on TN over the past 21 years, providing a meaningful reference for further exploration of topical issues and research trends in the field.